2018
DOI: 10.1370/afm.2230
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner–Physician Comanagement: A Theoretical Model to Alleviate Primary Care Strain

Abstract: PURPOSE Various models of care delivery have been investigated to meet the increasing demands in primary care. One proposed model is comanagement of patients by more than 1 primary care clinician. Comanagement has been investigated in acute care with surgical teams and in outpatient settings with primary care physicians and specialists. Because nurse practitioners are increasingly managing patient care as independent clinicians, our study objective was to propose a model of nurse practitioner-physician comanag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 31 publications
6
55
0
7
Order By: Relevance
“…Participants' proposed collaboration with other health professionals as a valuable strategy to alleviate GP time pressure and support PCC. This supports a recently published systematic review and qualitative investigation that reported collaborative care initiatives helped to alleviate individual GP workload, prevent GP burnout and support PCC (30). Our ndings add to the literature valuing the collaboration of care with other health professionals and a patient's social support network as supportive of PCC.…”
Section: Discussionsupporting
confidence: 87%
“…Participants' proposed collaboration with other health professionals as a valuable strategy to alleviate GP time pressure and support PCC. This supports a recently published systematic review and qualitative investigation that reported collaborative care initiatives helped to alleviate individual GP workload, prevent GP burnout and support PCC (30). Our ndings add to the literature valuing the collaboration of care with other health professionals and a patient's social support network as supportive of PCC.…”
Section: Discussionsupporting
confidence: 87%
“…Nurse practitioners and physicians may also jointly manage patients such that they each uniquely contribute to patients’ care and collaboratively share responsibilities based on patient needs and provider expertise. 46 For example, nurse practitioners caring for patients with complex clinical needs may center their care around disease management, care coordination, or symptom control following defined guidelines. 47 We found that patients with more chronic conditions had a greater number of visits when cared for by nurse practitioners than physicians.…”
Section: Discussionmentioning
confidence: 99%
“…5 One solution is that clinicians could team up with each other to comanage their panel and deliver more timely access to appointments for their patients. 7,8 A second solution is that clinicians could team up with nonclinician team members to reduce the need for FTE = clinician full-time equivalent value; r = correlation coefficient; SE = standard error.…”
Section: Discussionmentioning
confidence: 99%